2021
DOI: 10.1108/heswbl-07-2020-0169
|View full text |Cite
|
Sign up to set email alerts
|

Promoting entrepreneurship based on university students' perceptions of entrepreneurial attitude, university environment, entrepreneurial culture and entrepreneurial training

Abstract: PurposeThe purpose of this study is to verify some relationships between entrepreneurial attitude, university environment, entrepreneurial culture and entrepreneurial training, which can be used to promote entrepreneurship among university students.Design/methodology/approachA sample of 3,005 questionnaires answered by students from ten universities in Colombia was gathered and partial least squares structural equation modelling (PLS-SEM) was used for the analysis.FindingsThe results show that the more a stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 67 publications
(88 reference statements)
4
25
0
2
Order By: Relevance
“…The results confirmed that the campus learning environment mediated the relationship between the entrepreneurial curriculum (curriculum content, curriculum material, teaching strategies, and feedback and assessment) and entrepreneurial competencies, which approved our hypotheses H4a-H4d. These findings are in line with past research conducted on exploring the mediating effect of the entrepreneurial education on entrepreneurial attitudes (Barnes and de Villiers Scheepers, 2018;Lu et al, 2021;Luo et al, 2022;Valencia-Arias et al, 2022). Furthermore, Choi and Markham (2019) discussed the significance of the campus learning environment role to develop entrepreneurial competencies among the students as per the need of industry.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results confirmed that the campus learning environment mediated the relationship between the entrepreneurial curriculum (curriculum content, curriculum material, teaching strategies, and feedback and assessment) and entrepreneurial competencies, which approved our hypotheses H4a-H4d. These findings are in line with past research conducted on exploring the mediating effect of the entrepreneurial education on entrepreneurial attitudes (Barnes and de Villiers Scheepers, 2018;Lu et al, 2021;Luo et al, 2022;Valencia-Arias et al, 2022). Furthermore, Choi and Markham (2019) discussed the significance of the campus learning environment role to develop entrepreneurial competencies among the students as per the need of industry.…”
Section: Discussionsupporting
confidence: 87%
“…Luo et al (2022) conducted a study with 1,100 students in Guangdong, China, and found that the entrepreneurial environment is "the basis for the entrepreneurial project execution and can provide sufficient external conditions for the entrepreneurial activity implementation and concluded that a positive entrepreneurial environment can provide rich resources to support entrepreneurial activities and meet the elemental conditions required for the development of entrepreneurial projects." Furthermore, Valencia-Arias et al (2022) found that university environments equipped with tools that facilitate training and the development of entrepreneurial skills using different types of resources allow students to have better attitudes toward entrepreneurship. A campus environment that promotes entrepreneurship through experiential learning is shown to have positive outcomes on students' career aspirations and entrepreneurial abilities, through various studies, including those by Barnes and de Villiers Scheepers (2018) and Luo et al (2022).…”
Section: Mediation Effect Of Campus Learning Environmentmentioning
confidence: 99%
“…There is a direct relationship between the SS and ATE (H3). Consistent with the findings obtained in previous studies ( Anjum et al, 2020a ; Valencia-Arias et al, 2021 ). Bui Ngoc Tuan and Pham (2022) reported that the assistance provided by the outside world to the entrepreneurs themselves can reduce the difficulties in starting a business and thus have a positive attitude toward entrepreneurship.…”
Section: Discussionsupporting
confidence: 93%
“…The meta-analysis of entrepreneurship literature conducted by Hazarika et al (2020) also indicates that ATE has the strongest predictive potential for EI, accounting for more than half of the total variance. Valencia-Arias et al (2021) point out that although ATE is comprised of various motivations and varies depending on the individual, its impact on EI can be universal. Based on the literature, the following hypothesis is posited:…”
Section: Hypothesesmentioning
confidence: 99%
“…(Lawskiego & Pilichiewicza, 2018), (National.., 2021) 2. Entrepreneurial University: the international aspects of research Entrepreneurial university has responsibility to grew entrepreneurial intentions and potential of students (Turnea et al, 2020;Liu, & van der Sijde, 2021;Karim et al, 2022;Valencia-Arias et al, 2022).…”
Section: Introductionmentioning
confidence: 99%